Bullous Pemphigoid in a 53-Year-Old Man with Rapid Response to Corticosteroid Therapy: A Case Report (Medical Forum Monthly, 2026)
Bullous pemphigoid (BP) is an autoimmune disease marked by tense subepidermal bullae. The incidence of BP is very low and remains rarely reported. In Indonesia, there are no published data regarding the incidence or prevalence of BP. We report a 53-year-old male patient who presented with fluid-filled blisters involving almost the entire body, accompanied by pruritus for one month. Several blisters had ruptured, causing pain and a burning sensation. Dermatological examination revealed generalized multiple tense bullae filled with clear fluid, some of which were flaccid, arising on partially erythematous and partially normal skin. Most lesions had ruptured, resulting in erythematous macules, hyperpigmented and hypopigmented macules, and multiple erosions. Histopathological examination supported the diagnosis by demonstrating subepidermal bullae formation. The patient was treated with a combination of topical and oral corticosteroids and showed rapid clinical improvement within two months. Bullous pemphigoid has a good prognosis when treated adequately.